The evaluation of human sperm chromosomal status and the relation with sperm morphology, motility and fertilization in vitro - Claassens, Oswaldine Eleanor (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med. Cytology)) -- University of Stellenbosch, 1991.